Biophysics - Pattabhi, Vasantha; Gautham, N. (Alpha Science International Ltd., 2002)
This work not only addresses the needs of biologists and biochemists but also contains material for a one-semester course offered to Masters students of life sciences. It covers a range of topics from quantum mechanics to pre-biotic evolution